The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.est.5b03909
|View full text |Cite|
|
Sign up to set email alerts
|

Scientific Evidence Supports a Ban on Microbeads

Abstract: Growing scientific evidence indicates that synthetic plastic microbeads (hereafter, microbeads)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(190 citation statements)
references
References 0 publications
1
167
0
3
Order By: Relevance
“…There is now substantial action on this issue internationally, with several governments, including those of the USA and the UK, introducing legislative bans on microbeads in cosmetics and detergents, and many cosmetics companies voluntarily committing to halt their use of microplastics by 2020 [2,3]. New research on the effects of microbeads has revealed biological responses in both terrestrial and aquatic environments, with evidence demonstrating that microplastics reduce the survival and fitness of earthworms Lumbricus terrestris [4] and facilitate the accumulation of sorbed organic pollutants in fish [5].…”
Section: Aims Of Horizon Scanningmentioning
confidence: 99%
“…There is now substantial action on this issue internationally, with several governments, including those of the USA and the UK, introducing legislative bans on microbeads in cosmetics and detergents, and many cosmetics companies voluntarily committing to halt their use of microplastics by 2020 [2,3]. New research on the effects of microbeads has revealed biological responses in both terrestrial and aquatic environments, with evidence demonstrating that microplastics reduce the survival and fitness of earthworms Lumbricus terrestris [4] and facilitate the accumulation of sorbed organic pollutants in fish [5].…”
Section: Aims Of Horizon Scanningmentioning
confidence: 99%
“…Evidence is mounting that fibers are a dominant form of plastic pollution in many aquatic ecosystems-especially fluvial (McCormick et al, 2014;Zhao et al, 2014;Dris et al, 2015;Baldwin et al, 2016), but also in marine beaches and sediment (Browne et al, 2011;Claessens et al, 2011;Woodall et al, 2014;Fischer et al, 2015;Naidoo et al, 2015;. The ecological implications of these fibers remain to be shown, but plastic fibers are increasingly found in the stomachs and tissues of aquatic wildlife, many of which are consumed by larger animals, including humans (Neves et al, 2015;Rochman et al, 2015a;Vandermeersch et al, 2015;Li et al, 2016). Direct human health impacts have been reported, as well: when inhaled, microplastic fibers are retained the lung tissues and can become associated with malignant tumors (Pauly et al, 1998).…”
Section: Confidence In Fiber Count Data Depends On Size Class and Sormentioning
confidence: 99%
“…This plastic debris can be ranked as primary, in which the particle was manufactured as a microplastic, or secondary, in which the particle was manufactured as a macroplastic (>5 mm) and degraded to its present size (Cole et al 2011;Rummel 2014). Primary microplastics largely consist of microbeads (tiny round plastics mainly used as abrasive scrubs) and are commonly found in hygiene, sandblasting, and medical products (Zitko and Hanlon 1991;Patel et al 2009;Browne et al 2011;Rochman et al 2015). Secondary microplastics vary in form and origin, and often result from the breakdown of macroplastics through ultraviolet, microbial, and physical degradation (Browne et al 2007;Rios et al 2007;Moore 2008;Shah et al 2008;Barnes et al 2009;Ryan et al 2009;Andrady 2011).…”
Section: Introductionmentioning
confidence: 99%